Improved Second Generation Iron Pincer Complexes for Effective Ester Hydrogenation. Issue 5 (22nd January 2016) - Elangovan, Saravanakumar; Wendt, Bianca; Topf, Christoph; Bachmann, Stephan; Scalone, Michelangelo; Spannenberg, Anke; Jiao, Haijun; Baumann, Wolfgang; Junge, Kathrin; Beller, Matthias
Abstract: Hydrogenation of esters to alcohols with a well‐defined iron i Pr2 PNP pincer complex has been recently reported by us and other groups. We now introduce a novel and sterically less hindered Et2 PNP congener that provides superior catalytic activity in the hydrogenation of various carboxylic acid esters and lactones compared to the known complex. Successful hydrogenation proceeds under relatively mild conditions (60 °C) with lower catalyst loadings. Abstract :